Aplikasi IoT untuk Kendali Beban Listrik - Asnil Asnil; Krismadinata Krismadinata; Fivia Eliza; Irma Husnaini; Ricky Maulana (Jurnal Teknik Elektro Indonesia, 2020)
Internet of thing (IoT) is a system that will change the order of human life and industrial operations. In the future, objects that are operated daily with human interaction will be equipped with internet connectivity which is equipped with various sensors so that they are able to communicate and act on the information obtained without human intervention. The problem is that the ecosystem has not been fully developed as well as from the world of education which will prepare its human resources. Apart from that, the industrial sector which is predicted to be the largest user is still considering various things such as cost, security, non-conformity with the existing system and the ability of its resources. The system created is an effort to develop knowledge in the IoT field as an effort to bridge the need for human resources, especially at the Vocational High School (SMK) level. This IoT application for electrical load control is designed and built using the main components of NodeMcu V3, 4 channel relay, and Android with the Blynk application installed. Electrical load control commands are given using the Blynk application via Android and delivered to the NodeMcu V3 module using a Wifi intermediary and from NodeMcu V3 forwarded to 4 channel relays to control electrical loads in the form of ON and OFF. The results of the test show that the system built can operate properly in controlling electrical loads